Multidimensional Livelihood Vulnerability and Household Food Security: A Comparative Analysis of Urban and Peri-Urban Areas of Nepal - Kaphle, Basu Dev; Regmi, Punya Prasad; Dhakal, Shiva Chandra; Gauchan, Devendra (Journal of Agriculture and Forestry University, 2026)
Urban and peri-urban food security has received wide attention in recent years in the context of rapidly growing internal migration and urbanization in Nepal. This study was conducted to analyze the vulnerability to food insecurity in urban and peri-urban households of Nepal using the Livelihood Vulnerability Index (LVI) framework and the Household Food Insecurity Access Scale (HFIAS). Using a cross-sectional study design, data and information were collected from 435 households during January to March 2023, out of which 288 households were from different clusters of urban areas and 147 households from peri-urban areas of Kathmandu, Dhanusha, and Banke districts. The study found that overall livelihood vulnerability was higher in urban households (LVI = 0.401) than in peri-urban households (LVI = 0.282). Food insecurity, weak social networks, and limited livelihood diversification primarily drove urban vulnerability. Regarding the food security-related component, peri-urban households demonstrated relatively better food sufficiency. The association between LVI and food security categories was statistically significant in relation to urban and peri-urban households, indicating that higher vulnerability corresponds with severe food insecurity. The findings concluded that the public policy and programs need to focus on a location-specific and multidimensional approach to improve food security status and livelihood vulnerability.